External-electric-field-enhanced uniformity and deposition rate of a TiO2film prepared by the sparking process - W. Thongpan (2018)
© W. THONGPAN, T. KUMPIKA, E. KANTARAK, A. PANTHAWAN, P. POOSEEKHEAW, P. SINGJAI, A. TUANTRANONT, W. THONGSUWAN, 2018. We have used an external electric field to increase both the uniformity and deposition rate of TiO2films. The experiment is carried out by sparking-off titanium wires with a high dc voltage of 1 kV (field Eint= 10 kV/cm) and a limited current of 3 mA. The external electric fields (Eext) of 3, 6, and 9 kV/cm were applied to the sparking system for 1–5 hours. The as-deposited film morphology was characterized by scanning electron microscopy. The results clearly show that the films are only deposited on the external electric field area. Furthermore, the deposition rate of the films increased from 40.7% to 77.8% in the presence of the external electric field of 9 kV/cm. The effects of an external electric field on both the deposition rate and uniformity of films are investigated and described.